Inside Cover: Covalent Inhibition of New Delhi Metallo‐β‐Lactamase‐1 (NDM‐1) by Cefaclor (ChemBioChem 17/2014). Issue 17 (24th November 2014) - Thomas, Pei W.; Cammarata, Michael; Brodbelt, Jennifer S.; Fast, Walter
<x xml:space="preserve">Abstract</x> The inside cover picture shows The inside cover picture shows a visual metaphor for the unsuccessful use of covalent serine β‐lactamase inactivators to inhibit NDM‐1, which uses a noncovalent catalytic mechanism. In contrast, W. Fast and co‐workers (see p. 2541 ff.) have identified Lys211 as a suitable "handhold" for covalent inhibition. (Image by B. Lehmkuhle).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>